2008
DOI: 10.1093/aob/mcn202
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation and metal-binding characteristics of yellow lichen substances suggest a relationship with site preferences of lichens

Abstract: Metal complexation by lichen substances could be a prerequisite for lichen substance-mediated control of metal uptake. Assuming such an effect at pH values where the affinity of the metal for the lichen substance is intermediate would explain the strong preference of lichens with usnic or rhizocarpic acids to acidic substrata. Moreover, it would explain the preference of lichens with parietin and some lichens with compounds of the pulvinic acid group either for nutrient-rich substrata at low pH or for calcareo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 42 publications
(81 reference statements)
1
46
0
Order By: Relevance
“…However, although members of the same family (Parmeliaceae), both lichens differ in their morphology, which is also likely to affect element uptake. Complex formation of UA and Cu 2+ in the pH range preferred by UA-producing lichens (pH 3.5-6; Takani et al 2002;Hauck and Jürgens 2008;Hauck et al 2009) suggests that these complexes are involved in the observed promotion of Cu 2+ uptake. Whether such lipophilic complexes directly cross the phospholipid membrane (as proven for uncomplexed UA; Abo-Khatwa et al 1996;Hauck and Jürgens 2008) or Cu 2+ ions are transferred to transporters is unclear.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, although members of the same family (Parmeliaceae), both lichens differ in their morphology, which is also likely to affect element uptake. Complex formation of UA and Cu 2+ in the pH range preferred by UA-producing lichens (pH 3.5-6; Takani et al 2002;Hauck and Jürgens 2008;Hauck et al 2009) suggests that these complexes are involved in the observed promotion of Cu 2+ uptake. Whether such lipophilic complexes directly cross the phospholipid membrane (as proven for uncomplexed UA; Abo-Khatwa et al 1996;Hauck and Jürgens 2008) or Cu 2+ ions are transferred to transporters is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Given the multitude of compounds and their widespread ability to interact with metal ions (Hauck and Huneck 2007), it is likely that promotion of nutrient uptake will be seen in other lichen symbioses. Recent UV-spectroscopic studies in yellow and orange lichen substances, including UA, suggested that promotion of metal uptake by lichen substances might be widespread (Hauck et al 2009). Lichen compounds that occur in lichens of nutrient-poor sites form complexes with metal ions precisely at the pH ranges preferred by the respective lichens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the detected mineral deterioration may be related to the release of secondary metabolites such as pulvinic acid, the precursor of the crystalline deposits observed in the cortex layer and characterizing the Candelariella genus ( Culberson, 1979). Pulvinic acid, as oxalic acid, displays acidic and chelating functions that make it active in complexing metals, including Mg 2+ , Fe 2+ and Fe 3+ , in the alkaline range ( Hauck et al, 2009) which often characterizes water and soils deriving from serpentinized ultramafic rocks ( Alexander et al, 2007), including asbestos rich serpentinite sediments ( Schereier et al, 1987). Accordingly, the fibres produced upon incubation for 35 days with oxalic acid not only are similarly modified in their chemical composition to those colonized by C. vitellina, but are likely modified through a similar dissolution pathway, thus being suitable for testing the potency to release ROS of lichen deteriorated fibres.…”
Section: Discussionmentioning
confidence: 99%
“…A typical character of lichens is their ability to store large amounts of cations in the apoplast that can be taken up intracellularly with delay (Hauck et al 2006). Cation-binding sites in the cell wall and lichen secondary metabolites (Hauck et al 2009) are apparently involved in this process.…”
Section: Introductionmentioning
confidence: 99%